MENINGKATKAN KETERAMPILAN PROSES SAINS DAN KARAKTER WASAKA MENGGUNAKAN MODEL PROBLEM BASED LEARNING DAN TALKING STICK TERINTEGRASI STEM PADA MUATAN IPA SISWA KELAS V SEKOLAH DASAR - Ainul Aplah; Muhsinah Annisa (Refleksi Edukatika)
The aim of the research is to describe teacher activities, analyze student activities, WASAKA character, science process skills, and student learning outcomes. This research employs classroom action research. This study uses classroom action research with 22 students from Class VA at SDN Telawang 3 Banjarmasin during the 2023/2024 academic year. The sampling technique used is purposive sampling. The approach used is both qualitative and quantitative. Data analysis is calculated based on a percentage scale and the specified indicators of learning completeness. The research results showed that teacher activities scored 59, students' classical activities 91%, and classical science process skills 95%. These gains impacted classical cognitive learning outcomes at 100%, classical affective learning outcomes at 91%, and classical psychomotor learning outcomes at 95%. Based on these findings, it can be concluded that in science content, using the combination of Problem Based Learning and Talking Stick models integrated with STEM can improve teacher activity, student activity, science process skills, WASAKA character, and student learning outcomes. It is hoped that the combination of Problem Based Learning and Talking Stick models can be used as a reference to improve teacher activity, student activity, science process skills, WASAKA character, and student learning outcomes.